Assessment of drug attitude, medication adherence and quality of life among psychiatric patients in South Indian population: a cross sectional study - Ganesan, Suganya; Selvaraj, Nitya; Dass, Vinoth Krishna; Jayabalan, Nalinidevi; Rajamohammad, Meher Ali; Anandan, Isswariya (International Journal of Basic & Clinical Pharmacology, 2018)
Background: In spite of many progresses in treatment of psychiatric disorders, medication nonadherence plays an important role in worsening of clinical condition and affects quality of life among psychiatric patients. There are numerous factors contributing for medication nonadherence among patients with mental illness. So, this study was conducted to assess psychiatric patients’ adherence of medication and to improve their quality of life with psychiatric disorder. The objectives of the study were to analyze impact of pharmacophilia and pharmacophobia on medication adherence among patients with psychiatric disorders at a tertiary care hospital and to assess quality of life among pharmacophilic and pharmacophobic patients. Methods: A cross-sectional study was conducted in outpatient psychiatric department for a period of two months. After obtaining informed voluntary consent, patient’s socio-demographic details, diagnosis, and treatment were recorded from prescription slip. Patients above 18yr age with psychiatric diagnosis as per International Classification of Diseases 10 (ICD-10) and receiving at least one psychotropic medication for >1 month were enrolled in study and assessed using: Drug attitude inventory classification (DAI-10); Medication Rating Scale (MARS); Quality of life enjoyment and satisfaction Questionnaire-Short Form (Q-LES-Q-SF). Results: Among 130 patients, 116 were pharmacophilic and 14 were pharmacophobic as per DAI-10 scale. 81.9% of pharmacophilic were adherent to prescribed medication assessed using MARS scale only 14.3% were pharmacophobic. The quality of life was better in pharmacophilic compared to pharmacophobic group (p=0.002) using Q-LES-Q-SF. Conclusions: This study concluded that pharmacophilic patients have higher adherence and good quality of life index compared to pharmacophobic. Proper counselling of pharmacophobic patients by psychiatrists could improve adherence and QOL.